ANALISIS SOLVABILITAS DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2020 – 2024 - Fadillah Alsyka Hidayah Simangunsong; Heffi Christya Rahayu; Andi Afrizal (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study aims to analyze the effect of solvency and liquidity on financial performance in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Financial performance is measured using Return on Assets (ROA), while solvency is measured by Debt to Equity Ratio (DER) and liquidity by Current Ratio (CR). The study uses a quantitative approach with secondary data from annual financial reports with the sample used in this study being 6 (six) food and beverage companies listed on the Indonesia Stock Exchange (IDX) selected through purposive sampling technique. Data were analyzed using multiple linear regression with the help of SPSS version 21. The results of the study (1) Solvency (DER) does not have a significant effect on financial performance (ROA); (2) Liquidity (CR) has a positive and significant effect on financial performance; and (3) Simultaneously, solvency and liquidity together have a significant effect on financial performance. The implications of this study provide input for companies to further optimize liquidity management, as well as being a consideration for investors in assessing the company's financial health. Suggestions for further research are to add other variables and expand the scope of the period and industrial sectors.